PENERAPAN NILAI ISLAMI DALAM PELAYANAN FARMASI KLINIS: KAJIAN SISTEMATIS ETIKA, KEHALALAN DAN KEPUASAN PASIEN - Rozak, Miftahul; Saraswati, Damai Ira; Fathurohman SW, Oman; Salamah, Nina (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
Islamic pharmaceutical and healthcare services represent an innovative approach that integrates Islamic ethical values, such as justice, halal compliance, and patient satisfaction, into clinical practice. However, the application of these values faces challenges, including public knowledge gaps, insufficient training for healthcare professionals, and the lack of unified practice standards. This study employs a systematic review method to analyze relevant literature from the past decade. Literature searches were conducted using PubMed and Google Scholar with keywords such as